2018
DOI: 10.3389/fimmu.2018.01777
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Macrophages in the Resolution of Inflammation, Tissue Repair, and Tolerance to Infection

Abstract: Pathogen persistence in the respiratory tract is an important preoccupation, and of particular relevance to infectious diseases such as tuberculosis. The equilibrium between elimination of pathogens and the magnitude of the host response is a sword of Damocles for susceptible patients. The alveolar macrophage is the first sentinel of the respiratory tree and constitutes the dominant immune cell in the steady state. This immune cell is a key player in the balance between defense against pathogens and tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
212
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(216 citation statements)
references
References 78 publications
2
212
0
2
Order By: Relevance
“…Expression of myeloid cell genes in the airway also correlated with a signature of oxidative metabolism, which is characteristic of M2 macrophages and typically associated with control of tissue damage (Viola et al, 2019). However, in the context of pulmonary infection, polarization of AMs toward an anti-inflammatory M2 phenotype was found to promote continued inflammation, suggesting that these MΦs may not be effective at resolving anti-viral immunity (Allard et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of myeloid cell genes in the airway also correlated with a signature of oxidative metabolism, which is characteristic of M2 macrophages and typically associated with control of tissue damage (Viola et al, 2019). However, in the context of pulmonary infection, polarization of AMs toward an anti-inflammatory M2 phenotype was found to promote continued inflammation, suggesting that these MΦs may not be effective at resolving anti-viral immunity (Allard et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These findings, however, should be treated with caution, as genetic depletion of macrophages induces their death via necrosis and may induce tissue damage on its own (21). Single-cell RNA-Seq data may identify specific markers that can be used to more precisely target distinct macrophage populations to dissect their contributions to tissue injury and repair (76,(102)(103)(104)(105).…”
Section: The Journal Of Clinical Investigationmentioning
confidence: 99%
“…6. Blockade of EZH2 with 3-DZNeP suppresses the in vitro EMT in co-cultured BALF and mouse lung epithelial cell lines through regulation of the TGF-β/Smad signaling It has been reported that alveolar macrophages can interact with several other cell types such as epithelial, endothelial and immune cells during tissue repair and regeneration and brosis [24] , however the underlying mechanism remains incompletely understood. Since we observed that the M2-like macrophages were elevated while EMT was suppressed in the alveolus of 3-DZNeP-treated brotic mice, we hypothesized that there existed a crosstalk between macrophages and epithelial cells in the alveolar microenvironment.…”
Section: -Dznep Suppresses the In Vivo Emt By Inhibiting Activationmentioning
confidence: 99%